Derivation of terrain roughness indicators via granulometries - Tay, L. T.; Daya Sagar, B. S.; Chuah, H. T. (2005)
Digital elevation models (DEMs) provide rich clues about various geophysical and geomorphologic processes. These clues include conspicuous protrusions and intrusions of foreground and background portions that testify the presence of channels and ridges in DEMs. We show an application of greyscale granulometries to characterize DEMs through shape-size complexity measures relative to symmetric rhombus, octagon and square templates. We first compute pattern spectra that measure the size distributions of protrusions and intrusions in a DEM. We then employ pattern spectra to compute probability size distribution functions of protrusions and intrusions relative to three templates. We finally compute shape-size complexity measures of DEM by employing these probability functions. To illustrate the implementation of granulometric approach to compute these measures of both background and foreground, we consider an interferometrically generated DEM of a part of Cameron Highlands of Malaysia. Hierarchical watersheds that could be decomposed from DEMs can be better classified via these measures.